Pelatihan Pijat Bayi untuk Peningkatan Kesehatan dan Tumbuh Kembang Bayi pada Ibu di Kelurahan Bunder, Kecamatan Cikupa, Kabupaten Tangerang - Martini, Titin; Ajeng, Atnesia; Wahyuni, Titis; Oktaviani, Ika (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Infant massage is a touch stimulation that has many benefits for the health and growth of infants, including increased weight gain, sleep quality, and emotional bonding between mother and baby. Based on a preliminary study in Bunder Village, Cikupa District, Tangerang Regency, it was found that most mothers do not have adequate knowledge and skills regarding correct and safe infant massage techniques. The purpose of this community service activity is to provide practical knowledge and skills to mothers in Bunder Village about infant massage. The implementation method includes interactive counseling, demonstrations, and direct practice of infant massage guided by expert speakers. This activity was carried out on [Implementation Date, e.g.: August 18, 2024] at [Implementation Location, e.g.: Bunder Village Community Hall] involving [Number of Participants, e.g.: 35] mothers. The evaluation results showed a significant increase in mothers' understanding and skills regarding infant massage. It is hoped that this training can improve the practice of infant massage at home, contribute to optimal health and growth of infants, and strengthen the emotional bond between mothers and their babies.